Degradable sanitary towel

By using specific combinations of materials in the degradable sanitary napkin, the problems of poor antibacterial performance and insufficient degradation performance in the prior art are solved, and more efficient degradation and better user experience are achieved.

CN119838043AInactive Publication Date: 2025-04-18SHANGHAI YUEYUESHU WOMENS PROD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510336042.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antibacterial performance of existing degradable sanitary napkins is poor, and the degradation performance needs to be further improved.

Method used

A degradable base film consisting of polylactic acid, poly-butylene terephthalic acid-adipate, functional fillers, modified starch, lignin and antibacterial fillers is used to form a complete structure of degradable sanitary napkin.

Benefits of technology

It improves the antibacterial properties and degradation speed of sanitary napkins, enhances the strength and toughness of the material, maintains flexibility and breathability, and reduces potential harm to the environment and the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838043A_ABST
    Figure CN119838043A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable sanitary napkin, and relates to the technical field of sanitary napkin degradable materials, and the sanitary napkin structurally comprises a surface layer, an absorption core body and a degradable bottom film from top to bottom, the degradable bottom film is prepared from the following raw materials in parts by weight: 75 to 90 parts of base material, 2.5 to 5 parts of functional filler, 7.5 to 16 parts of modified starch, 0.5 to 2.5 parts of lignin, 2 to 4.5 parts of antibacterial filler and 5 to 10 parts of plasticizer. According to the degradable sanitary napkin, the functional filler is added, so that treated zeolite can be used as a reinforcing phase, the strength and toughness of a polylactic acid / poly (terephthalic acid)-butylene adipate composite material are improved, and the sanitary napkin is not prone to deformation and fracture in the using process; after the surface of the zeolite is treated, some active sites can be introduced to promote the reaction of lactide, dimethyl sulfoxide and other systems, and the functional filler is added into the polylactic acid / poly (terephthalic acid)-butylene adipate, so that the degradation speed of the material in the natural environment can be increased, and the long-term pollution to the environment can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sanitary napkin degradable materials, in particular to a degradable sanitary napkin. Background Art

[0002] Sanitary napkins are a type of sanitary product used by women during menstruation. The main materials are cotton, non-woven fabrics, wood pulp, high-absorbent resins, or polymers and polymer composite paper formed by composites of the above materials.

[0003] Referring to the Chinese patent for a degradable sanitary napkin and its preparation method (Announcement No.: CN117717642A), it includes a surface layer, which is formed by electrospinning 8-15wt% polylactic acid ethyl acetate solution. Its preparation method includes the following steps: (1) preparing a spinning solution: adding polylactic acid to ethyl acetate and stirring evenly under constant temperature stirring conditions; controlling the temperature to 30-40°C, the stirring speed to 300-800 rpm, and the stirring time to 8-10 hours; preparing 8-15wt% polylactic acid ethyl acetate solution; (2) electrospinning: electrospinning the above polylactic acid ethyl acetate solution; the sanitary napkin of the invention can be rapidly degraded in the natural environment after use, reducing the environmental burden; due to its good air permeability, consumers will feel more comfortable and less uncomfortable during use; in addition, the surface layer of the sanitary napkin is thinner and softer, further improving the comfort during use. However, the antibacterial performance of the sanitary napkin prepared by the above-mentioned prior art is relatively poor, and the degradation performance needs to be further improved; therefore, the present invention proposes a degradable sanitary napkin to solve the above-mentioned problems. Summary of the invention

[0004] 1. Technical issues to be resolved In view of the deficiencies of the prior art, the present invention provides a degradable sanitary napkin, which solves the problems mentioned in the above background technology.

[0005] (II) Technical solution To achieve the above objectives, the present invention is implemented by the following technical scheme: a degradable sanitary napkin, the sanitary napkin structure comprises a surface layer, an absorbent core and a degradable bottom film from top to bottom, the degradable bottom film comprises the following raw materials in parts by weight: 75-90 parts of a base material, 2.5-5 parts of a functional filler, 7.5-16 parts of a modified starch, 0.5-2.5 parts of lignin, 2-4.5 parts of an antibacterial filler, and 5-10 parts of a plasticizer; Wherein, the surface layer is a polylactic acid fiber nonwoven fabric surface layer or a pure cotton surface layer, and the absorbent core is a composite of at least one of pure cotton cloth or pure wood pulp and a highly absorbent resin; The substrate comprises polylactic acid and polybutylene terephthalate-adipate, and the mass ratio thereof is 5:(1-2), and the plasticizer is tributyl citrate; The preparation method of the functional filler is: (1) Pour 150 mL of hydrochloric acid solution into 10-14.5 g of zeolite, heat in a water bath, stir, and then cool to room temperature; (2) Wash with deionized water until the pH value is neutral, then pour into 500 mL of deionized water, and ultrasonically treat at 50%-70% ultrasonic power for 5-7 minutes at room temperature, then filter and dry in a drying oven; (3) Mix 25-32 mL of dimethyl sulfoxide and 10-12.5 g of lactide, raise the temperature to 80-90° C., and stir until completely dissolved to prepare solution A; (4) Add 25-28 mL of dimethyl sulfoxide and 10-14 g of 4-dimethylaminopyridine to the dried zeolite, heat the oil bath to 85-95°C, and under the protection of nitrogen atmosphere, pour solution A into the mixture, heat the mixture to 130-145°C, and react for 20-24 hours; (5) After the reaction is completed, wash with anhydrous ethanol for 3-5 times, then filter, and then place in a drying oven to dry to obtain the functional filler.

[0006] Preferably, in said (1), the concentration of hydrochloric acid is 0.03-0.05 mol / L, the temperature is raised to 70-80°C, and stirred for 2-4 hours.

[0007] Preferably, in (2) and (5), the drying temperature is 55-65° C. and the drying time is 6-8 h.

[0008] Preferably, the modified starch preparation method is: Ⅰ. Pour 12-15.2g of xylitol and 0.03-0.046g of p-toluenesulfonic acid into 100mL of toluene, and then place in a drying oven at 100-110°C for 1.5-2h under the protection of nitrogen atmosphere; Ⅱ. Add 48.6-52.2g of nonanoic acid and 0.08-0.15g of p-toluenesulfonic acid, raise the temperature to 130-145°C, and stir to react for 2.5-3.5h; III. After the reaction is completed, the reaction product is washed and then distilled under reduced pressure; IV. Stir the distilled product and dried corn starch for 1-3 minutes, and then place it in a sealed condition for 20-24 hours to obtain modified starch.

[0009] Preferably, in said III, the reaction product is washed 2-4 times with saturated sodium bicarbonate solution, saturated sodium chloride solution and deionized water in sequence.

[0010] Preferably, in said IV, the corn starch is dried in a vacuum drying oven at 75-85°C, the mass ratio of the reaction product to the corn starch is 1:(4.8-5), and the stirring speed is 800-1200r / min.

[0011] Preferably, the preparation method of the antibacterial filler is: S1. Add 3.5-5 g of dimethylaminoethyl methacrylate, 35 g of isobornyl methacrylate and 0.12-0.18 g of azobisisobutyronitrile to 160 mL of tetrahydrofuran, and perform ultrasonic treatment at constant temperature under sealed conditions until the mixture is completely dissolved. S2, heat the oil bath to 60-70°C, react for 10-12 hours, and then cool naturally to room temperature; S3, add 6.6-7.5g of 1,3-propane sultone, and react for 20-24h; S4. After the reaction is completed, the temperature is raised to 40-50°C for rotary evaporation, the product is washed with methanol for 3-4 times, then filtered, and finally placed in a drying oven at 60-70°C for 20-24 hours to obtain an antibacterial filler.

[0012] Preferably, in S1, the constant temperature is 50-60°C.

[0013] (III) Beneficial effects The present invention provides a degradable sanitary napkin. Compared with the prior art, it has the following beneficial effects: (1) The degradable sanitary napkin, by adding functional fillers, allows the treated zeolite to serve as a reinforcing phase, thereby improving the strength and toughness of the polylactic acid / polybutylene terephthalate-adipate composite material, making the sanitary napkin less likely to deform and break during use; and after the zeolite surface is treated, some active sites are introduced to promote the reaction of lactide with dimethyl sulfoxide and other systems. The addition of functional fillers to polylactic acid / polybutylene terephthalate-adipate can accelerate the degradation rate of the material in the natural environment and reduce long-term pollution to the environment. Compared with traditional non-degradable materials and some materials containing more chemical residues, it is safer and more environmentally friendly, reducing potential harm to the human body and the environment; since polylactic acid / polybutylene terephthalate-adipate itself has good flexibility and air permeability, the addition of a series of treated zeolites and related reaction products will not reduce its flexibility and air permeability while improving other properties of the material, but will further optimize it, making the sanitary napkin more comfortable when in contact with the skin and reducing the feeling of stuffiness and discomfort.

[0014] (2) The degradable sanitary napkin has multiple hydroxyl groups and good hydrophilicity, so the prepared modified starch can improve the hydrophilicity of the polylactic acid / polybutylene terephthalate-adipate composite material, so that the degradable sanitary napkin can absorb menstrual blood faster and keep the surface dry. Since corn starch itself has a certain rigidity, it can be added to polylactic acid / polybutylene terephthalate-adipate as a reinforcing phase to improve the strength and toughness of the composite material, making the sanitary napkin more durable and less prone to damage during use. At the same time, the ingredients in the modified starch, such as corn starch, are biodegradable, relatively safe and non-toxic, reducing potential irritation and harm to human skin. Adding modified starch to the polylactic acid / polybutylene terephthalate matrix of the degradable sanitary napkin can promote the degradation of the material in the natural environment, making it easier for microorganisms to attach and decompose the area where the modified starch is located, thereby accelerating the degradation rate of the entire composite material and reducing the long-term impact on the environment.

[0015] (3) The antibacterial filler added to the degradable sanitary napkin can attract and destroy the cell membrane and cell wall structure of bacteria, thereby inhibiting the growth and reproduction of bacteria, effectively inhibiting the growth of microorganisms after contact with menstrual blood, reducing the generation of odor, keeping the sanitary napkin clean and hygienic, and reducing the risk of users suffering from diseases caused by microbial infection; at the same time, the antibacterial filler can play a certain role in isolation and lubrication between the molecular chains of polylactic acid / polybutylene terephthalate-adipate, reducing the interaction force between the molecular chains, so that the material has better flexibility and plasticity, and can better fit the curve of the human body during use, thereby improving the comfort of the user; because the antibacterial material itself has a polymer network with a certain cross-linked structure, when added to polylactic acid / polybutylene terephthalate-adipate, it can form a reinforced skeleton inside the composite material, significantly improving the physical properties of the degradable sanitary napkin material such as tensile strength, tear strength and wear resistance, making the degradable sanitary napkin more durable during use and not easily damaged by external forces such as stretching and friction, thereby ensuring the normal use function and protective effect of the sanitary napkin. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a comparison chart of the degradation performance test provided by the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] In this application, the superabsorbent resin adopts the material in the GB / T 22875-2018 standard.

[0019] Example 1 (1) The preparation method of the functional filler is as follows: pour 150 mL of a 0.03 mol / L hydrochloric acid solution into 10 g of zeolite, heat it to 70 °C in a water bath, stir it for 2 h, and then cool it to room temperature; wash it with deionized water until the pH value is neutral, then pour it into 500 mL of deionized water, and ultrasonically treat it at 50% ultrasonic power for 5 min at room temperature, then filter it, and then dry it in a drying oven at 55 °C for 6 h; add 25 mL of dimethyl Mix 10 g of lactide with methyl sulfoxide, heat to 80°C, and stir until completely dissolved to obtain solution A; add 25 mL of dimethyl sulfoxide and 10 g of 4-dimethylaminopyridine to the dried zeolite, heat the oil bath to 85°C, and pour solution A into it under the protection of nitrogen atmosphere, heat it to 130°C, and react for 20 hours; after the reaction is completed, wash it with anhydrous ethanol for 3 times, then filter it with suction, and then dry it in a drying oven at 55°C for 6 hours to obtain a functional filler; (2) The preparation method of modified starch is as follows: 12 g of xylitol and 0.03 g of p-toluenesulfonic acid are poured into 100 mL of toluene, and then placed in a drying oven at 100°C for drying and dehydration for 1.5 h under the protection of a nitrogen atmosphere; 48.6 g of nonanoic acid and 0.08 g of p-toluenesulfonic acid are added, the temperature is raised to 130°C, and the reaction is stirred for 2.5 h; after the reaction is completed, the reaction product is washed twice with a saturated sodium bicarbonate solution, a saturated sodium chloride solution and deionized water in sequence, and then vacuum distilled; the corn starch is placed in a vacuum drying oven at 75°C for drying, the distilled product and the dried corn starch are stirred and mixed at a mass ratio of 1:4.8 at a speed of 800 r / min for 1 min, and then placed in a sealed condition for 20 h to obtain the modified starch; (3) The preparation method of the antibacterial filler is as follows: 3.5 g of dimethylaminoethyl methacrylate, 35 g of isobornyl methacrylate and 0.12 g of azobisisobutyronitrile are added to 160 mL of tetrahydrofuran in sequence, and the mixture is subjected to constant temperature ultrasonic treatment at 50°C under sealed conditions until it is completely dissolved; the oil bath is heated to 60°C, reacted for 10 hours, and then naturally cooled to room temperature; 6.6 g of 1,3-propane sultone is added and reacted for 20 hours; after the reaction is completed, the mixture is heated to 40°C and rotary evaporated, the product is washed three times with methanol, then filtered, and finally dried in a drying oven at 60°C for 20 hours to obtain the antibacterial filler; (4) 78 g of polylactic acid and polybutylene terephthalate-adipate with a mass ratio of 5:1 were placed in a ventilated drying oven at 40°C and dried for 3 h, then poured into a high-speed mixer, and then 10 g of tributyl citrate, 5 g of functional filler, 16 g of modified starch, 2.5 g of lignin, and 4.5 g of antibacterial filler were added and blended for 10 min. The uniformly mixed materials were added into a parallel twin-screw extruder for extrusion, water cooling, and pelletization to form pellets; wherein the main engine speed of the twin-screw extruder was 500 rpm / min, the feeding frequency was 15 Hz, the extrusion temperature was 160°C, and the pellets were dried at 80°C for 8 h; the dried pellets were blown into film by a film blowing machine to obtain a degradable film; the specific process parameters of the film blowing machine were: the set temperature of the film blowing machine was controlled at 200°C, the main engine speed was 80 rpm / min, and the traction speed was 6 m / min; Example 2 (1) The preparation method of the functional filler is as follows: pour 150 mL of a 0.04 mol / L hydrochloric acid solution into 12.5 g of zeolite, heat it to 75 °C in a water bath, stir it for 3 h, and then cool it to room temperature; wash it with deionized water until the pH value is neutral, then pour it into 500 mL of deionized water, and ultrasonically treat it at 60% ultrasonic power for 6 min at room temperature, then filter it, and then dry it in a drying oven at 60 °C for 7 h; add 28 mL of dimethyl Mix 11.5 g of lactide with dimethyl sulfoxide, heat to 85°C, and stir until completely dissolved to obtain solution A; add 26 mL of dimethyl sulfoxide and 12 g of 4-dimethylaminopyridine to the dried zeolite, heat the oil bath to 90°C, and pour solution A into it under the protection of nitrogen atmosphere, heat to 135°C, and react for 22 hours; after the reaction is completed, wash with anhydrous ethanol for 4 times, then filter, and then place in a drying oven at 60°C for 7 hours to obtain a functional filler; (2) The preparation method of modified starch is as follows: 14 g of xylitol and 0.04 g of p-toluenesulfonic acid are poured into 100 mL of toluene, and then placed in a drying oven at 105°C for drying and dehydration for 1.8 h under the protection of a nitrogen atmosphere; 50 g of nonanoic acid and 0.1 g of p-toluenesulfonic acid are added, the temperature is raised to 135°C, and the reaction is stirred for 3 h; after the reaction is completed, the reaction product is washed three times with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then vacuum distilled; the corn starch is placed in a vacuum drying oven at 80°C for drying, the distilled product and the dried corn starch are stirred and mixed at a mass ratio of 1:4.9 at a speed of 1000 r / min for 2 min, and then placed in a sealed condition for 22 h to obtain the modified starch; (3) The preparation method of the antibacterial filler is as follows: 4 g of dimethylaminoethyl methacrylate, 35 g of isobornyl methacrylate and 0.15 g of azobisisobutyronitrile are added to 160 mL of tetrahydrofuran in sequence, and the mixture is subjected to constant temperature ultrasonic treatment at 55°C under sealed conditions until it is completely dissolved; the oil bath is heated to 65°C, reacted for 11 hours, and then naturally cooled to room temperature; 7 g of 1,3-propane sultone is added and reacted for 22 hours; after the reaction is completed, the mixture is heated to 45°C and rotary evaporated, the product is washed with methanol 4 times, then filtered, and finally dried in a drying oven at 65°C for 22 hours to obtain the antibacterial filler; (4) 84.5 g of polylactic acid and polybutylene terephthalate-adipate in a mass ratio of 5:1.5 were placed in a ventilated drying oven at 40°C and dried for 3 h, then poured into a high-speed mixer, and then 7 g of tributyl citrate, 3.5 g of functional filler, 10 g of modified starch, 1.5 g of lignin, and 3 g of antibacterial filler were added and blended for 10 min. The uniformly mixed materials were added to a parallel twin-screw extruder for extrusion, water cooling, and pelletization to form pellets; wherein the main engine speed of the twin-screw extruder was 500 rpm / min, the feeding frequency was 15 Hz, the extrusion temperature was 160°C, and the pellets were dried at 80°C for 8 h; the dried pellets were blown into film by a film blowing machine to obtain a degradable film; the specific process parameters of the film blowing machine were: the set temperature of the film blowing machine was controlled at 200°C, the main engine speed was 80 rpm / min, and the traction speed was 6 m / min.

[0020] Example 3 (1) The preparation method of the functional filler is as follows: 150 mL of a 0.05 mol / L hydrochloric acid solution is poured into 14.5 g of zeolite, the mixture is heated to 80 °C in a water bath and stirred for 4 h, and then cooled to room temperature; the mixture is washed with deionized water until the pH value is neutral, and then poured into 500 mL of deionized water, and ultrasonically treated at 70% ultrasonic power for 7 min at room temperature, and then filtered and dried in a drying oven at 65 °C for 8 h; 32 mL of dimethyl Mix 12.5 g of lactide with methyl sulfoxide, heat to 90°C, and stir until completely dissolved to obtain solution A; add 28 mL of dimethyl sulfoxide and 14 g of 4-dimethylaminopyridine to the dried zeolite, heat the oil bath to 95°C, and pour solution A into it under the protection of nitrogen atmosphere, heat it to 145°C, and react for 24 hours; after the reaction is completed, wash it with anhydrous ethanol for 5 times, then filter it with suction, and then dry it in a drying oven at 65°C for 8 hours to obtain a functional filler; (2) The preparation method of modified starch is as follows: 15.2 g of xylitol and 0.046 g of p-toluenesulfonic acid are poured into 100 mL of toluene, and then placed in a drying oven at 110°C for drying and dehydration for 2 h under the protection of a nitrogen atmosphere; 52.2 g of nonanoic acid and 0.15 g of p-toluenesulfonic acid are added, the temperature is raised to 145°C, and the reaction is stirred for 3.5 h; after the reaction is completed, the reaction product is washed 4 times with a saturated sodium bicarbonate solution, a saturated sodium chloride solution, and deionized water, and then vacuum distilled; the corn starch is placed in a vacuum drying oven at 85°C for drying, the distilled product and the dried corn starch are stirred and mixed at a mass ratio of 1:5 at a speed of 1200 r / min for 3 min, and then placed in a sealed condition for 24 h to obtain the modified starch; (3) The preparation method of the antibacterial filler is as follows: 5 g of dimethylaminoethyl methacrylate, 35 g of isobornyl methacrylate and 0.18 g of azobisisobutyronitrile are added to 160 mL of tetrahydrofuran in sequence, and the mixture is subjected to constant temperature ultrasonic treatment at 60°C under sealed conditions until it is completely dissolved; the oil bath is heated to 70°C, reacted for 12 hours, and then naturally cooled to room temperature; 7.5 g of 1,3-propane sultone is added and reacted for 24 hours; after the reaction is completed, the mixture is heated to 50°C and rotary evaporated, the product is washed with methanol 4 times, then filtered, and finally dried in a drying oven at 70°C for 24 hours to obtain the antibacterial filler; (4) 84 g of polylactic acid and polybutylene terephthalate (PET) with a mass ratio of 5:2 were placed in a ventilated drying oven at 40°C and dried for 3 h, then poured into a high-speed mixer, and then 5 g of tributyl citrate, 2.5 g of functional filler, 7.5 g of modified starch, 0.5 g of lignin, and 2 g of antibacterial filler were added and blended for 10 min. The uniformly mixed materials were added into a parallel twin-screw extruder for extrusion, water cooling, and pelletization to form pellets; wherein the main engine speed of the twin-screw extruder was 500 rpm / min, the feeding frequency was 15 Hz, the extrusion temperature was 160°C, and the pellets were dried at 80°C for 8 h; the dried pellets were blown into film by a film blowing machine to obtain a degradable film; the specific process parameters of the film blowing machine were as follows: the set temperature of the film blowing machine was controlled at 200°C, the main engine speed was 80 rpm / min, and the traction speed was 6 m / min.

[0021] Comparative Example 1 Compared with Example 1, the difference is that no functional filler is added; the rest remains unchanged.

[0022] Comparative Example 2 Compared with Example 1, the difference is that modified starch is not added; the rest remains unchanged.

[0023] Comparative Example 3 Compared with Example 1, the difference is that no antibacterial filler is added; the rest remains unchanged.

[0024] Sample preparation: Use polylactic acid fiber non-woven fabric as the surface layer, pure cotton cloth, pure wood pulp and high absorbent resin as the absorbent core, and bond the surface layer, the absorbent core and the degradable bottom film from top to bottom in sequence to make a degradable sanitary napkin.

[0025] Antibacterial performance test: The antibacterial performance of the film was tested with two pathogenic bacteria, Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus). The antibacterial test was as follows: the sample was placed in a disposable sterile plate with sterile tweezers, and the prepared bacterial suspension was diluted to 10 with LB liquid culture medium. 6 CFU / mL, then draw 200μL of diluted bacterial solution and add it to the sample, place the sterile plate in a constant temperature incubator, and culture it at 37℃ for 18h. After the culture is completed, the above common culture medium is diluted 10 times with a sterilized PBS solution, and fermented on LB solid culture medium with 100mL of diluent at a constant temperature of 37℃ for 18h to test the antibacterial rate; the results are shown in Table 1.

[0026] Tensile properties test: The test was carried out in accordance with GB / T 1040.1-2018 standard, and the average value was taken after 5 tests; the results are shown in Table 1.

[0027] Table 1 Degradation performance test: The sample was weighed and buried in the soil. The average temperature during the test was 16.5±5℃ and the relative humidity was 68±10%. It was taken out every two weeks, cleaned with deionized water and dried in an oven at 60℃ for 4 hours. The weight change was recorded and the weight loss rate was calculated. The sample size was 5mm×2mm×0.2mm. The results were as follows: Figure 1 As shown: compared with comparative examples 1-2, the weight loss rate of the samples in Examples 1-3 is significantly improved, and compared with comparative examples 1-2, the sample in comparative example 3 also has obvious weight loss.

[0028] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0029] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0030] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A degradable sanitary napkin, which comprises a surface layer, an absorbent core and a degradable bottom film from top to bottom, characterized in that: The degradable base film comprises the following raw materials in parts by weight: 75-90 parts of base material, 2.5-5 parts of functional filler, 7.5-16 parts of modified starch, 0.5-2.5 parts of lignin, 2-4.5 parts of antibacterial filler, and 5-10 parts of plasticizer; Wherein, the surface layer is a polylactic acid fiber nonwoven fabric surface layer or a pure cotton surface layer, and the absorbent core is a composite of at least one of pure cotton cloth or pure wood pulp and a highly absorbent resin; The substrate comprises polylactic acid and polybutylene terephthalate-adipate, and the mass ratio thereof is 5:(1-2), and the plasticizer is tributyl citrate; The preparation method of the functional filler is: (1) Pour 150 mL of hydrochloric acid solution into 10-14.5 g of zeolite, heat in a water bath, stir, and then cool to room temperature; (2) Wash with deionized water until the pH value is neutral, then pour into 500 mL of deionized water, and ultrasonically treat at 50%-70% ultrasonic power for 5-7 minutes at room temperature, then filter and dry in a drying oven; (3) Mix 25-32 mL of dimethyl sulfoxide and 10-12.5 g of lactide, raise the temperature to 80-90° C., and stir until completely dissolved to prepare solution A; (4) Add 25-28 mL of dimethyl sulfoxide and 10-14 g of 4-dimethylaminopyridine to the dried zeolite, heat the oil bath to 85-95°C, and under the protection of nitrogen atmosphere, pour solution A into the mixture, heat the mixture to 130-145°C, and react for 20-24 hours; (5) After the reaction is completed, wash with anhydrous ethanol for 3-5 times, then filter, and then place in a drying oven to dry to obtain the functional filler.

2. A degradable sanitary napkin according to claim 1, characterized in that: In the above (1), the concentration of hydrochloric acid is 0.03-0.05 mol / L, the temperature is raised to 70-80°C, and stirred for 2-4 hours.

3. A degradable sanitary napkin according to claim 1, characterized in that: In (2) and (5), the drying temperature is 55-65°C and the drying time is 6-8h.

4. A degradable sanitary napkin according to claim 1, characterized in that: The modified starch preparation method is: Ⅰ. Pour 12-15.2g of xylitol and 0.03-0.046g of p-toluenesulfonic acid into 100mL of toluene, and then place in a drying oven at 100-110°C for 1.5-2h under the protection of nitrogen atmosphere; Ⅱ. Add 48.6-52.2g of nonanoic acid and 0.08-0.15g of p-toluenesulfonic acid, raise the temperature to 130-145°C, and stir to react for 2.5-3.5h; III. After the reaction is completed, the reaction product is washed and then distilled under reduced pressure; IV. Stir the distilled product and dried corn starch for 1-3 minutes, and then place it in a sealed condition for 20-24 hours to obtain modified starch.

5. A degradable sanitary napkin according to claim 4, characterized in that: In the above III, the reaction product is washed 2-4 times with saturated sodium bicarbonate solution, saturated sodium chloride solution and deionized water in sequence.

6. A degradable sanitary napkin according to claim 4, characterized in that: In said IV, the corn starch is placed in a vacuum drying oven at 75-85°C and dried, the mass ratio of the reaction product to the corn starch is 1:(4.8-5), and the stirring speed is 800-1200r / min.

7. The degradable sanitary napkin according to claim 1, characterized in that: The preparation method of the antibacterial filler is: S1. Add 3.5-5 g of dimethylaminoethyl methacrylate, 35 g of isobornyl methacrylate and 0.12-0.18 g of azobisisobutyronitrile to 160 mL of tetrahydrofuran, and perform ultrasonic treatment at constant temperature under sealed conditions until the mixture is completely dissolved. S2, heat the oil bath to 60-70°C, react for 10-12 hours, and then cool naturally to room temperature; S3, add 6.6-7.5g of 1,3-propane sultone, and react for 20-24h; S4. After the reaction is completed, the temperature is raised to 40-50°C for rotary evaporation, the product is washed with methanol for 3-4 times, then filtered, and finally placed in a drying oven at 60-70°C for 20-24 hours to obtain an antibacterial filler.

8. A degradable sanitary napkin according to claim 7, characterized in that: In S1, the constant temperature is 50-60°C.

Citation Information

Patent Citations

  • Degradable sanitary towel and preparation method thereof

    CN117717642A

  • PBAT / PLA starch-based completely biodegradable material and preparation method thereof

    CN111410822A

  • Bio-based dehydrated xylitol ester plasticizer and preparation method thereof

    CN112778242A

  • Method for catalyzing ring-opening polymerization of lactide by using Lewis acid-base pair

    CN113527652A

  • Straw for milk and preparation method thereof

    CN118459957A